2006
DOI: 10.1021/la0601399
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Mercapto Ligand Exchange on the Surface of FePt Nanoparticles

Abstract: Tailoring the surface of nanoparticles is essential for biological applications of magnetic nanoparticles. FePt nanoparticles are interesting candidates owing to their high magnetic moment. Established procedures to make FePt nanoparticles use oleic acid and oleylamine as the surfactants, which make them dispersed in nonpolar solvents such as hexane. As a model study to demonstrate the modification of the surface chemistry, stable aqueous dispersions of FePt nanoparticles were synthesized after ligand exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
143
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 28 publications
5
143
0
1
Order By: Relevance
“…[20] Johnson et al has recently shown the possibility of place exchanging the oleyl amine ligand with thiols and the oleic acid ligand with a different carboxylic acid. [21] Detailed FT-IR and X-ray photoelectron spectroscopy (XPS) measurements showed the presence of oleic acid on the surface of the FePt NPs even after place exchange reactions with dodecanthiol. Place exchange reactions with mercaptoalkanoic acid showed the presence of sulfur in a form other than thiolate pointing to the fact that these ligands attach to the surface also through the carboxylic acid.…”
mentioning
confidence: 99%
“…[20] Johnson et al has recently shown the possibility of place exchanging the oleyl amine ligand with thiols and the oleic acid ligand with a different carboxylic acid. [21] Detailed FT-IR and X-ray photoelectron spectroscopy (XPS) measurements showed the presence of oleic acid on the surface of the FePt NPs even after place exchange reactions with dodecanthiol. Place exchange reactions with mercaptoalkanoic acid showed the presence of sulfur in a form other than thiolate pointing to the fact that these ligands attach to the surface also through the carboxylic acid.…”
mentioning
confidence: 99%
“…To stabilize MNP character, chemical coating on naked MNP surface was developed [14][15][16]. For example, MNP with 10-20 nm can be stabilized in 2-aminoethanethiol (0.5 M) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments to carboxylate the {SiW 11 Fe}-Fe 2 Pt core-shell nanoparticles via a ligand exchange reaction based on mercapto-undecanoate (MUA) following the description by H. G. Bagaria et al 42 result in the core-shell nanoparticles being stripped of their polyoxometalate shell in addition to the organic ligands oleic amine and oleyl acid ( Fig. 5(III) and (IV)).…”
mentioning
confidence: 99%